When new media meets an old regulatory structure: the development of IPTV and the challenge of media policy. (1st January 2013) - Son, Chang Yong
Media policy is currently coming under pressure due to the arrival of the convergence era. Convergence technology has blurred distinct devices, services, and industry sectors, and it has even been blamed for destroying the media market. The convergence era is associated with the digital revolution and it provides opportunities for media corporations to generate revenue. However, convergence calls for policy makers to reconsider the existing regulatory framework. Consequently, media policy makers are currently wrestling with the challenges cause by convergence and the digital era. This paper explores their responses to these challenges, focusing on internet protocol television as a typical type of converged service. This paper also explores the challenge of setting media policy in the convergence era by examining the formulation of regulatory framework over the IPTV in Korea. In addition, this paper examines conflicting interests and politics over emerging new services from contesting stakeholders. In doing so, it argues that the conventional regulatory structure has lost legitimacy if the government fails to address the converged service. It also finds that media policy should be flexible to coordinate the contrasting interests of stakeholders in the competitive market.